Influence of Digital Media Platform for Information Transmission of Lembaga Zakat Negeri Kedah (LZNK), Malaysia - Faryna Mohd Khalis; Kartini Kasim; Wan Noor Faaizah Wan Omar; Hafizah Zainal (Environment-Behaviour Proceedings Journal, 2025)
Digital media has emerged as a new platform for virtual communication and transactions, including the payment of zakat, a mandatory act for Muslims. Despite the automation of zakat since 1991, public awareness remains low due to insufficient communication and publicity. Additionally, management issues hinder financially disadvantaged individuals from receiving assistance. Hence, the study aimed to identify the most effective digital media platform for managing zakat in Kedah, using surveys targeted at academics from Universiti Teknologi MARA. The findings indicate that Lembaga Zakat Negeri Kedah’s official website is frequently visited, and infographics are the most effective tool for promoting Zakat.